Digitalisasi Wisata Halal melalui Aplikasi Smartphone Dimasa Pendemi Covid-19 - Lukmanul Hakim (Journal of Islamic Management, 2021)
The potential of Indonesian Halal Tourism is in great demand by foreign tourists, in the current Covid-19 period, one of the most visible influences is the internet. The Internet has become a liaison for the whole world in carrying out its activities. During the Covid-19 pandemic, a platform in the form of a digital application is needed that can load all destinations, from places, lodging, food, and facilities owned by tourist attractions that are labeled halal tourism to restore tourist visits. It aims to find out how to develop Halal Tourism Applications on Smart Phones (android/OS). This writing uses library research (library research), and is qualitative, descriptive analysis. The results of the discussion show that the Potential for Transforming Digitalization to an easy and efficient smartphone, strengthening digital infrastructure in the form of services and qualified human resources, increasing synergies between stakeholders that strengthen policies that are able to encourage the acceleration of digitalization, and branding halal tourism by conducting the "Halal Lifestyle Literacy Campaign".